Persepsi Ibu Terhadap Kondisi Lingkungan Sosial Sebagai Faktor Risiko Kegemukan Pada Anak Prasekolah - Ika Agustina; I Made Alit Gunawan; Madarina Julia (JURNAL NUTRISIA, 2016)
Background: the prevalence of obesity in children in Indonesia keeps increasing every year. One of the reasons is the low level of physical activity due to the length of time children's Playground outdoors increasingly declining. Long play time outside the House which the increasingly brief thought to be influenced by the social environment in the community. Objective: Analyze the relationship of maternal perception towards social environmental conditions with obesity in preschoolers Methods: this research is a case control study. The case was identified obese preschoolers (Z score based on w/TB > 2 SD), the control is a child who is not obese (Z score based on w/TB-2 Z-score < ≤ 2 SD) with a matching age and gender. The location of the research was the city with the selection of the sample using the method of Probability Proportional to size (PPS). The number of sample cases and controls of each group was 101 people (1:1). The statistical analysis was performed using t-test, analysis and testing of Mc Nemar. Result: a group of children obese mother who has a positive social environment berpersepsi play outdoors 26.46 minutes longer (95 CI 7,18-45,74). The risk of overweight children who play outdoors less than 2 hours and have the mother berpersepsi negatively to social environmental conditions is 2.05 (95 CI 1,09-3.9). Social environmental conditions is an effect modifier for the relationship between long time playing outdoors and overweight in preschoolers in Yogyakarta. Conclusion: children's play time is influenced by the perception of the mother against the social environmental conditions. The negative perception of the mother on the social environmental conditions will lower the long play time outside the House, raising the risk of overweight children. Keywords: obesity, social environment, play outdoors, preschoolers